(untitled) (Emancipação, 2010)
Este artigo pretende delinear os contornos do que Georg Lukács chama de “movimento de decadência ideológica da burguesia”, o qual significa uma passagem no plano da teoria da racionalidade ao formalismo e que corresponde à passagem no plano político da revolução à manutenção para a classe burguesa. Analisaremos as suas consequências especialmente na economia política e na Sociologia. A ideia desenvolvida é que tanto a dissolução da economia clássica quanto o nascimento da Sociologia são dois lados de uma mesma moeda: fazem parte do que Lukács chamou de “destruição da razão burguesa”. Para concluir, a análise a ser feita será a propósito da herança cultural do pensamento progressista burguês. Palavras-chave: Marxismo. Economia política. Sociologia. Abstract: This article aims at delineating the outlines of what Georg Lukács calls “movement of ideological decay of the bourgeoisie”, which means a transition in the theoretical plan from the rationality to the formalism that corresponds to the transition in the political plan from the revolution to the maintenance for the bourgeois class. The analysis will focus especially on its consequences in terms of political economy and sociology. The idea developed is that the dissolution of the traditional economy as the birth of sociology represents two sides of the same coin, being part of what Lukács called the “destruction of bourgeois reason”. In conclusion, the following analysis will examine the cultural inheritance of the bourgeois progressive thought. Keywords: Marxism. Political economy. Sociology.